Implementation of helical wave propagation motion in snake robot moving on exterior of a pipe. (17th April 2019) - Qi, Wei; Kamegawa, Tetsushi; Gofuku, Akio
In this study, we developed a snake robot that goes through a branch point on exterior of a pipe in a helical shape. A hyperbolic function is utilised to generate a wave along the helical curve. The joint angles of the snake robot are derived by calculating the curvature and torsion of the curve by using the formula of the continuous curve model. We implemented the new motion in a real snake robot by considering parameters of the curve. In addition, we propose a method to compensate for the effect of gravity to achieve the motion by a real snake robot. Experimental results are shown to validate the effectiveness of the proposed method.